Dual-threshold-voltage two-port sub-threshold SRAM cell apparatus - Chang, Mu-Tien; Huang, Po-Tsang; Hwang, Wei (My University, 2010)
The invention relates to a dual-threshold-voltage two-port sub-threshold SRAM cell apparatus. The above-mentioned apparatus comprises a first inverter, a second inverter, an access transistor and a read buffer. The first inverter and the second inverter include a plurality of first operating elements and a plurality of second operating elements for storing data. The access transistor is coupled to the first inverter and the second inverter, wherein the first operating elements and the second operating elements are high threshold voltage operating elements and the access transistor is low threshold voltage operating transistor. The read buffer is used for performing a read operation.